Assessment of the impact of social media marketing attributes on consumer subscribe intention and instagram performance of netflix Indonesia - Nooryawan, Muhammad Naafi; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract. Netflix is a world-leading media services. They offer thousands of movies and TV series, including its own produced series through its subscription video on demand (SVOD) service. In entering the Indonesian market, Netflix Indonesia opts for an atypical social media marketing (SMM) approach compared to its Indonesian market competitors. However, despite the differentiation strategy, it does not result in a remarkable growth of users. This study aimed to examine how SMM will influence the subscribe intention among Netflix Indonesia Instagram audience. Then, the result will be used to assess and give recommendations on Netflix Indonesia SMM practice recommendation to improve its consumer subscribe intention through its Instagram. A quantitative survey was conducted among 209 respondents who have interacted with Netflix Indonesia on Instagram within the three months data collection period. The results indicate that SMM is significantly related to consumer subscribe intention. It further demonstrates that customer engagement is a full mediator and perceivedvalue is a partial mediator in how SMM influence subscribe intention. This study implies that SVOD service marketers should pay more attention to creating contents that correspond with the audience liking and preference to ensure higher engagement that will stimulate subscribe intention as a result. The academic and management implications based on the empirical results of this study is expected to enhance marketer understandings on how SMM could improve subscribe intention and maximize its potential. Keywords: Netflix Indonesia, subscription video on demand, SMM, subscribe intention, social media engagement, perceived value.